Effect of vitamin E level and dietary zinc source on performance and intestinal health parameters in male broilers exposed to a temperature challenge in the finisher period. Issue 4 (30th December 2020) - De Grande, Annatachja; Ducatelle, Richard; Delezie, Evelyne; Rapp, Christof; De Smet, Stefaan; Michiels, Joris; Haesebrouck, Freddy; Van Immerseel, Filip; Leleu, Saskia
Abstract: The objective of this study was to evaluate the interaction of zinc source (ZnSO4 vs. zinc amino acid complex) and vitamin E level (50 IU vs. 100 IU) on performance and intestinal health of broilers exposed to a temperature challenge in the finisher period. A total of 1224 day old male Ross 308 broilers were randomly distributed among 4 dietary treatments (9 replicates per treatment). Dietary treatments were organized in a 2 × 2 factorial arrangement: two sources of zinc, 60 mg/kg of Zn as ZnSO4 .7H2 O or 60 mg/kg of Zn as zinc amino acid complexes (ZnAA) combined with two levels of vitamin E (50 or 100 IU/kg). Zinc and vitamin E were added to a wheat/rye‐based diet that was designed to create a mild nutritional challenge. From day 28 until day 36 (finisher period), all birds were subjected to chronic cyclic high temperatures (32°C ± 2°C and RH 55–65% for 6 h daily). The combination of ZnAA and 50 IU/kg of vitamin E improved weight gain in the starter (day 0–10), finisher (day 28–36) and overall period (day 0–36) and feed conversion ratio in the starter (day 0–10) and finisher phase (day 28–36). Providing Zn as ZnAA significantly improved villus length and villus/crypt ratio in the starter, grower and finisher period and decreased infiltration of T‐lymphocytes and ovotransferrin leakage in the finisher period. In conclusion, providing broilers with a diet supplemented with ZnAA and a vitamin E level of 50 IU/kg, resulted in better growth performance as compared to all other dietary treatments. Interestingly, under the conditions of this study, positive effects of ZnAA on performance did not occur when vitamin E was supplemented at 100 IU/kg in feed. Moreover, providing zinc as zinc amino acid complex improved intestinal health.